Pharmaceutical drug promotion: perception and attitude of medical interns towards drug company interactions in a tertiary care teaching hospital - N. G., Chandan; N. S., Shashikumar; H., Nagabushan (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Interactions of pharmaceutical industry with the physicians which are usually mediated through pharmaceutical representatives have a significant impact on physician decision-making. This interaction can start as early as medical school during their training and this is said to influence their prescribing behavior when they become physicians. Aims and objectives of the study was to evaluate the attitude of interns towards pharmaceutical companies interactions including accepting gifts, ethical issues and influence on clinical decisions and also to study perception of medical interns towards the accuracy of information provided by the medical representatives. Methods: This was a cross sectional questionnaire based study that was conducted among the medical interns of the teaching hospital attached to Mandya Institute of Medical Sciences, Mandya. The study was carried out between July and August 2016. A preformed structured questionnaire was distributed to the interns consenting to participate in the study. Completed questionnaires were collected, compiled and data was analyzed. Results: A total of 93 questionnaires were distributed and 90 interns responded (response rate 96.7%). About 44.4% respondents felt that accepting gifts from Drug Company would influence their own decision making. Only 26.6% of them were of the opinion that it is ethical to accept pharmaceutical company gifts. Majority of them felt that Medical Representatives exaggerate the benefits of medicines and downplay the risks and contraindications of medicine. About 32.2% of them were of the opinion that they would prefer to prescribe the drug from the companies offering them with gifts over those without. Majority of the respondents felt that the doctors should be offered with gifts by drug companies whenever their drugs are prescribed. Conclusions: Attitude of Medical Interns towards Drug Company interactions as observed suggests for training the budding doctors on appropriate drug company interactions to prevent the risks associated with promotional efforts of pharmaceutical companies.